2012
DOI: 10.1021/mp300448k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptide-Capped Gold Nanoparticles as Drug Delivery Systems

Abstract: A number of cyclic peptides were synthesized and evaluated as simultaneous reducing and capping agents for generation of cyclic peptide-capped gold nanoparticles (CP-AuNPs). Among them, direct dissolution of cyclic peptides containing alternate arginine and tryptophan [WR](n) (n = 3-5) into an aqueous solution of AuCl(4)(-) led to the formation of CP-AuNPs, through the reducing activity of tryptophan residues and attraction of positively charged arginine residues toward chloroaurate anions in the reaction envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…46 We found out that the combination of tryptophan and positively charged amino acids worked as reducing/capping agents and led to the formation of in-situ functionalized metal nanoparticles.…”
Section: Peptide Nanostructuresmentioning
confidence: 97%
“…46 We found out that the combination of tryptophan and positively charged amino acids worked as reducing/capping agents and led to the formation of in-situ functionalized metal nanoparticles.…”
Section: Peptide Nanostructuresmentioning
confidence: 97%
“…Confocal microscopy revealed the localization of fluorescence-labeled-3TC in the presence of c[KW] 5 -AuNPs mostly in nucleus in SK-OV-3 cells after 1 h. On the other hand, l(KW) 5 -AuNPs delivered fluorescence-labeled-3TC in cytoplasm. Furthermore, c[KW] 4 -AuNPs offered two major advantages over c[RW] 4 -AuNPs that we previously reported 15 . First, the reaction time for the formation of c[KW] 4 -AuNPs (1 h) was significantly shorter compared to that of c[RW] 4 -AuNPs (4-8 h).…”
Section: Resultsmentioning
confidence: 88%
“…15 Incubation of F′-l(KW) 5 -AuNPs and F′-c[KW] 5 -AuNPs with SK-OV-3 cells showed 3.3- and 4.3-fold higher cellular uptake compared to the corresponding fluorescently-labeled peptides F′-l(KW) 5 and F′-c[KW] 5 , respectively, thus suggesting the formation of P-AuNPs is crucial for the enhanced cellular permeability (Figure 5). FACS results confirmed that F′-c[KW] 5 -AuNPs showed approximately 1.6-fold higher cellular uptake than F′-l(KW) 5 -AuNPs, suggesting that the cyclic nature of the peptide in P-AuNPs contributes to improving the cellular uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that conjugation of gemcitabine with polypeptide may improve its plasma stability and sustain the drug release profile (Kiew et al, 2010[21]). In recent years, numerous natural and synthetic CPPs, such as Tat, transportan, and polyamino acids (e.g., poly-arginines), were discovered or designed for intracellular delivery of anticancer agents (Gupta et al, 2011[19]; Nasrolahi Shirazi et al, 2013[31]). Among these CPPs, TAT peptide and poly-arginine are the most frequently used for the delivery of various molecules such as proteins, peptides, RNA, therapeutic and imaging compounds into cells (Shirazi et al, 2014[39]; Tsumuraya and Matsushita, 2014[42]).…”
Section: Introductionmentioning
confidence: 99%